2021
DOI: 10.1073/pnas.2012578118
|View full text |Cite
|
Sign up to set email alerts
|

Human variation in gingival inflammation

Abstract: Oral commensal bacteria actively participate with gingival tissue to maintain healthy neutrophil surveillance and normal tissue and bone turnover processes. Disruption of this homeostatic host–bacteria relationship occurs during experimental gingivitis studies where it has been clearly established that increases in the bacterial burden increase gingival inflammation. Here, we show that experimental gingivitis resulted in three unique clinical inflammatory phenotypes (high, low, and slow) and reveal that interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(97 citation statements)
references
References 68 publications
(78 reference statements)
13
84
0
Order By: Relevance
“…We found the highest bacterial community diversity in gingival fluid for those reporting often or always to bleed from the gums when they brushed their teeth. This is in line with studies on experimental gingivitis showing an increase in community diversity during transition from periodontal health to periodontitis (Kistler et al, 2013; Bamashmous et al, 2021). We found that those who reported the highest frequency of gingival bleeding had a lower abundance of the bacteria within the Firmicutes and Actinobacteria phyla.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found the highest bacterial community diversity in gingival fluid for those reporting often or always to bleed from the gums when they brushed their teeth. This is in line with studies on experimental gingivitis showing an increase in community diversity during transition from periodontal health to periodontitis (Kistler et al, 2013; Bamashmous et al, 2021). We found that those who reported the highest frequency of gingival bleeding had a lower abundance of the bacteria within the Firmicutes and Actinobacteria phyla.…”
Section: Discussionsupporting
confidence: 88%
“…We found that those who reported the highest frequency of gingival bleeding had a lower abundance of the bacteria within the Firmicutes and Actinobacteria phyla. These are typically gram‐positive phyla, which are also found to decrease in relative abundance during the onset of experimental gingivitis (Bamashmous et al, 2021). Although we cannot confirm the presence of gingivitis among our study participants, a recent study found that self‐reported questions regarding bleeding gums performed quite well in sensitivity towards gingival inflammation, as confirmed with bleeding on probing assessed by trained staff (Goulão et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different clinical responses in the periodontium to bacterial burden may shed light on COVID clinical responses to SARS-CoV-2 virus challenges. These host inflammatory clinical responses to oral bacteria were designated as "high", "low", and "slow" [22]. The high clinical response group to similar bacterial concentrations resulted in high IL-1β levels in inflamed tissues.…”
Section: Pathogenesis and Cellular Mechanism Of Actionmentioning
confidence: 99%
“…The high clinical response group to similar bacterial concentrations resulted in high IL-1β levels in inflamed tissues. Applying this model to COVID-19 infected individuals, the varying levels of inflammatory response may be a plausible explanation for non-vaccinated individuals being at varying levels of risk for pulmonary "cytokine storms", resulting in outcomes from hospitalizations to possible death [22]. The clinical presentation of SARS-CoV-2 infections are often asymptomatic or have mild to moderate symptoms; 5% or less develop multi-organ failure or acute respiratory distress syndrome.…”
Section: Pathogenesis and Cellular Mechanism Of Actionmentioning
confidence: 99%